Prospecting of anti-Candida bioactive in Origanum vulgare L. artisanal essential oil (Research, Society and Development, 2021)
Candida albicans is a yeast belonging to the normal microbiota of the human body, considered the most pathogenic species of the genus. It is the main microorganism related to candidiasis. Essential oils of Origanum vulgare have phenolic compounds, such as thymol and carvacrol, which have an effective antimycobacterial character at certain concentrations, but little is known about its biological activity in artisanal preparation. Thus, we evaluated the resistance of standard strains of opportunistic yeast C. albicans against in vitro antifungal activity of artisanal extract of O. vulgare. An inoculum of the challenger was subjected to different concentrations of the fungicidal agent in solidified Muller Hinton and broth followed by incubation at 35°C. The oil was prepared in a manner similar to a possible homemade procedure, and was further sterilized to ensure homogeneity of the indicator. The readings were performed in two days every 24 hours so that there were different possible moments of growth. The tests, which occurred in triplicate, showed that, under experimental conditions, the yeast was resistant to the essential oil compounds at all observed concentrations. Morphological variation was observed in both colonies and yeast cells. Based on analyzes, the artisanal essential oil is incorporated as a promising candidate for the development of antimycotics for clinical use, although in vivo tests are required.